Four decades of research on religious tourism: prevalent themes and future research area - Vaishali Singh; Anjan Bhuyan (Research in Hospitality Management)
This study aims to review and provide a comprehensive analysis on religious tourism from 1979 to 2024. It conducts a systematic literature review using the SPAR-4-SLR protocol and other bibliometric analytical techniques. Using performance analysis, the study unpacks the research applications and methods used, the top contributing journals, countries, and regions of religious tourism. By applying factorial analysis and thematic evolution in R, the study presents thematic areas uncovered in religious tourism. Using science mapping, this article conducts a co-occurrence analysis to map the knowledge clusters in VOSviewer. Finally, the article also proposes directions for future research using content analysis.